Internal Control System Analysis of Merchandise Inventory Process at PT. Midi Utama Indonesia Tbk Manado Branch - Tuerah, Raykes Hinrich; Toweula, Alpindos; Korompis, Sintia N; Sahibondang, Gloria Treisya (CV. Rayyan Dwi Bharata, 2023)
Inventory is very important in supporting the operational activities of trading companies. Internal control aims to protect company assets that are vulnerable to damage, fraud and theft. This research was conducted at PT Midi Utama Indonesia Tbk Manado branch. The purpose of this study is to determine the application of internal control over merchandise inventory and whether the internal control over merchandise inventory has been running effectively and efficiently. The research method used in this research is descriptive qualitative which is described in the form of internal control system data in which there are types of inventory, purchasing procedures and merchandise expenditure. The results of the research show that internal control over merchandise inventory as a whole has been going well. This is indicated by the existence of an organizational structure that clearly separates the functions and responsibilities of inventory management, as well as a well-implemented authority system and procedure for recording inventory transactions. Recommendations for the organizational structure so that the company can maintain the separation of duties and responsibilities of each of its parts. And to prevent errors in recording goods, those in an overshit position must make notes to the personnel who will replace them, then conduct training and improve strict supervision and good control, so that employees can understand and apply what has become the provisions of the company.